1997
DOI: 10.1080/026990597123647
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of computer-assisted cognitive rehabilitation for persons with traumatic brain injury

Abstract: This study examined the efficacy of computer-assisted cognitive rehabilitation (CACR) in persons with traumatic brain injury (TBI). Twenty persons with TBI who received hierarchically based CACR following inpatient neurorehabilitation were compared to a group of 20 persons with TBI matched for age, education, days in coma and time between testing. The comparison group received various other therapies including speech therapy and occupational therapy. The difference between pre- and post-treatment neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 19 publications
1
28
0
9
Order By: Relevance
“…The training program—computer-assisted cognitive rehabilitation—arranged the trainings in a hierarchical manner with tasks increasing in complexity over time. 26 Similarly, Serino et al 45 demonstrated significant improvements in working memory, divided attention, and executive function compared with a general stimulation control group following a training program based on the PASAT. Ponsford and Kinsella 41 also utilized a computer program composed of tasks that measure both accuracy and speed of responses over time.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The training program—computer-assisted cognitive rehabilitation—arranged the trainings in a hierarchical manner with tasks increasing in complexity over time. 26 Similarly, Serino et al 45 demonstrated significant improvements in working memory, divided attention, and executive function compared with a general stimulation control group following a training program based on the PASAT. Ponsford and Kinsella 41 also utilized a computer program composed of tasks that measure both accuracy and speed of responses over time.…”
Section: Resultsmentioning
confidence: 96%
“…26,34,39,41,44,45,48 A class I study compared computerized attention training with a paper-and-pencil memory training control group. The computerized attention training program focused on visual, auditory, and divided attention, with task difficulty varying depending on number of stimuli, similarity between targets and distractors, and interstimulus intervals.…”
Section: Resultsmentioning
confidence: 99%
“…It is a child-friendly/adolescent version of the computerized CogRehab system (Chen et al, 1997) which was originally developed for adults with brain injury, but which has been used extensively with adults with schizophrenia (Bell et al, 2001; Hogarty et al, 2004; Kurtz et al, 2007) and individuals exhibiting learning disabilities/attention deficits (Bracy et al, 1999). …”
Section: Methodsmentioning
confidence: 99%
“…At present, cognitive training mainly includes traditional cognitive retraining and computer-assisted cognitive training, e.g. [29]. Computer-assisted cognitive training allows automation of many cognitive training procedures, making it possible to meet demand for care, improve stimulation quality, increase patient record reliability and optimize performance in impaired functions [30, 31].…”
Section: Introductionmentioning
confidence: 99%